El laicismo y la libertad de enseñanza en el Congreso Constituyente de 1916-1917: Una contribución para la comprensión del Estado moderno como garante de la laicidad y la libertad religiosa - Albor Guzmán, Saúl Manuel; Aguilar Camacho, Mario Jesús; Lozano Montero, Eva (Acta Universitaria, 2019)
The constitutional project of Article 3 debated in the Constituent Congress of 1916-1917 laid the foundations of laicism in education, not only public but also private. In the current context of the modern constitutionalism, human rights such as the right to education and the freedom of thought, conscience and religion, in the lay state, possess an even international protection, and so it is important to study the historical foundations of these constitutional laws. This article will analyze the Constitutional Article 3 that, from its origins, restricted the freedom of education due to the ideology of laicism that influenced from its first draft and that persists today. In the final discussion, the consequences of laicism, in the current debate on these fundamental human rights, and how education has been evolving from laicism are analyzed. Laicism still encloses neopositivist conceptual categories.